Prediction of periodontal disease: modelling and validation in different general German populations. (5th January 2014) - Zhan, Yiqiang; Holtfreter, Birte; Meisel, Peter; Hoffmann, Thomas; Micheelis, Wolfgang; Dietrich, Thomas; Kocher, Thomas
Abstract Aim To develop models for periodontitis using self‐reported questions and to validate them externally. Methods The Study of Health in Pomerania (SHIP‐0) was used for model development. Periodontitis was defined according to the definitions of the Center for Disease Control and Prevention‐American Academy of Periodontology, the 5th European Workshop in Periodontology, and Dietrich et al. (≥2 teeth with inter‐proximal clinical attachment loss of ≥4 mm and 6 mm as moderate and severe periodontitis) respectively. These models were validated in SHIP‐Trend and the Fourth German Oral Health Study (DMS IV). Results Final models included age, gender, education, smoking, bleeding on brushing and self‐reported presence of mobile teeth. Concordance‐statistics (C‐statistics) of the final models from SHIP‐0 were 0.84, 0.82 and 0.85 for the three definitions respectively. Validation in SHIP‐Trend revealed C‐statistics of 0.82, 0.81 and 0.82 respectively. As bleeding on brushing and presence of mobile teeth were unavailable in DMS IV, reduced models were developed. C‐statistics of reduced models were 0.82, 0.81 and 0.83 respectively. Validation in DMS IV revealed C‐statistics of 0.72, 0.78 and 0.72 for the three definitions respectively. All p values of the goodness‐of‐fit tests were >0.05. Conclusions The models yielded a moderate usefulness for prediction of periodontitis.